Natural rubber latex coated coarse wool fabric composite—Preparation, characterization, and application - Jose, Seiko; Paduvilan, Jibin Keloth; Prasad, Ananthu; Thomas, Sabu; Kadam, Vinod; George, Sneha (Polymer engineering and science, 2025)
The current study discusses the preparation and characterization of green composite from coarse wool fabric and natural rubber (NR) latex. Natural rubber latex was coated on the coarse wool fabric by the hand lay‐up method and vulcanized to form a flexible composite sheet. Standard techniques were used to determine the physicomechanical parameters, including areal density, thickness, solvent diffusion, and abrasion resistance. Scanning electron microscopy was used to analyze the morphology of the fracture surfaces. The composite sample was further analyzed using Fourier transform infrared spectroscopy to determine changes in the chemical structure. The viscoelastic properties of the composite were investigated using a dynamic mechanical analyzer. The aging of the composite with respect to accelerated temperature, UV radiation, and soil burial was also investigated through standard methods. The developed coarse wool–rubber latex composite was found quite flexible, unlike conventional stiff fiber‐reinforced composites. The scanning electron microscopy images depicted that rubber latex infiltrated the wool fabric matrix. The solvent diffusion studies showed slow penetration of water and toluene inside the composite due to a dense network of natural rubber inside the wool fabric. During the soil burial test, the composite lost 13% of its weight. A clutch bag and a shoulder bag were developed using the prepared composite. The newly developed coarse wool–NR latex composite has potential uses in technical textiles, conveyor belts, and fashion accessories. Highlights Natural rubber (NR) latex was coated on the coarse wool fabric and vulcanized. The wool–NR latex composite showed excellent physico‐mechanical properties. The thermal and UV aging properties were also found to be good. The developed composite is flexible, derived purely from natural sources, and inexpensive. The wool–NR latex composite could find potential applications in fashion accessories. Application of natural rubber latex on wool fabric and its characterization.